A Direct Test of Rock's Model of the Pricing of Unseasoned Issues - KOH, Francis (Institutional Knowledge at Singapore Management University, 1989)
Unique data availability and institutional arrangements for new issues in Singapore allow a direct test of the empirical implications of Rock's model of pricing unseasoned new issues. Our empirical results are consistent with the model. Specifically we find that the unseasoned new issues' anomaly disappears when the rationing associated with new issues is incorporated into the analysis. The winner's curse is evident in allocation patterns used in Singapore.